Unusual algal turfs associated with the rhodophyta Phyllophora crispa: Benthic assemblages along a depth gradient in the Central Mediterranean Sea. (5th February 2017) - Bonifazi, Andrea; Ventura, Daniele; Gravina, Maria Flavia; Lasinio, Giovanna Jona; Belluscio, Andrea; Ardizzone, Gian Domenico
Abstract: Macroalgal assemblages dominated by the turf-forming alga Phyllophora crispa are described in detail for the first time in the Central Mediterranean Sea. This particular form of algal growth, which comprises an upper mixed layer of multiple algal species with a basal stratum formed by entangled thalli of P. crispa, was observed for the first time in 2012 along the promontory of Punta del Lazzaretto (Giglio Island, Italy). In this study, this assemblage was analysed to document the diversity of macroalgae and invertebrate associated communities and assess their distribution along a depth gradient. The algae forming turfs grow directly on the rock at low depth up to 10–15 m depth, while they grow above P. crispa from 15 m to 35 m depth, resulting in luxuriant beds covering up to 100% of the substrate. Multivariate analysis revealed clear differences regarding algae and invertebrate species richness and abundance between shallow and deep strata because of the dominance of Phyllophora crispa at depths greater than 20 m. The long laminal thalli of P. crispa favoured sessile fauna colonization, while the vagile species were principally linked to the architectural complexity of the turf layer created by the P. crispa, which increased the microhabitat diversity and favoured sediment deposition within the turf layer. The complex structures of these turf assemblages and their widespread distribution along the whole coast of the island suggest a well-established condition of the communities linked to the high natural sedimentation rate observed in the area. Highlights: First report of macroalgal turf-forming assemblages dominated by the red seaweed Phyllophora crispa in Mediterranean waters. Increasing of microhabitat complexity deeply influence the invertebrates' communities. No evidence of water pollution were identified as driven factors influencing turfs development. High sedimentation rates could promote the establishment of stable turf-dominated algal and invertebrates assemblages.